PHYTOCHEMICAL ANALYSIS AND EVALUATION OF ANTIMICROBIAL POTENTIAL OF Senna alata LINN LEAVES EXTRACT - C, Karthika; K, MOHAMED RAFI; S, MANIVANNAN (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective:The objective of the present work is to evaluate the presence of phytochemical constituents and antimicrobial activity of different extracts from the leaves of Senna alata Linn. Methods: The serial exhaustive extraction was done with variousof solvents: Aqueous, Chloroforms, Ethanol, Methanol, Acetone, Benzene, Petroleum ether with increasing polarity using soxhlet apparatus. The phytochemical analysis was done by using the standard procedure. Antimicrobial activity was evaluated by disc diffusion method by using leaves extract against various human pathogens.Results: The results revealed that the leaves extracts contain Flavonoids, Terpenoids, Tannins, Phlobatannins, Saponins, Cardiac glycosides, Carbohydrate, Protein and Anthraquinones in major proportion. Aqueous extract was shown to be more effective against all the organisms followed by ethanol, chloroform, methanol, acetone, benzene, petroleum ether extracts. Salmonella typhi (28mm), Bacillus subtilis (28mm) was found to be most sensitive organism followed by Pseudomonas fluorescence (27mm), Escherichia coli (27mm). Conclusions: It can be concluded that the different extracts of Senna alata leaves extract contain a broad spectrum of secondary metabolites and also exhibit antimicrobial activity against all the tested microorganisms. Further phytochemical research is needed to identity the active product of S. alata may serve as leads in the development of new pharmaceuticals.